2015
DOI: 10.1371/journal.pone.0139162
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Knowledge of Venous Thromboembolism Prophylaxis among the Medical Staff of Intensive Care Units in North China

Abstract: BackgroundGuideline concordance for venous thromboembolism (VTE) prophylaxis in critically ill patients in intensive care units (ICUs) varies across different countries.ObjectiveTo explore how the medical staff of ICUs in China comprehend and practice VTE prophylaxis.MethodQuestionnaires comprising 39 questions and including 4 dimensions of thromboprophylaxis were administered in ICUs in North China.ResultsIn all, 52 ICUs at 23 tertiary hospitals in 7 Chinese provinces and municipalities were surveyed. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…Only 31.2% of participants had good knowledge of GCS and the percentage of participants who had a good grasp of each item was less than one-third, which further suggests that the knowledge level of clinically applying GCS among medical staff is low. The survey results of Tang et al [ 6 ] showed that only 10.3% of the medical staff knew the appropriate indications for medical VTE prophylaxis (e.g., GCS and intermittent pneumatic compression). As Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only 31.2% of participants had good knowledge of GCS and the percentage of participants who had a good grasp of each item was less than one-third, which further suggests that the knowledge level of clinically applying GCS among medical staff is low. The survey results of Tang et al [ 6 ] showed that only 10.3% of the medical staff knew the appropriate indications for medical VTE prophylaxis (e.g., GCS and intermittent pneumatic compression). As Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al explored how the medical staff of intensive care units in China comprehend and practice VTE prophylaxis. In the questioned group of 1861 physicians and nurses, 36.5% of physicians and 22.2% of nurses were aware of the VTE guidelines, and 19.0% of physicians and 9.5% of nurses comprehended the latest ACCP Guideline edition (9 th Edition -2012) -37.6% of the medical staff chose the VTE prophylaxis method based on the related guidelines [14].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the current literature shows that a lack of awareness and knowledge of VTE prophylaxis and management is not limited to any location or medical specialty. Tang et al [14] in 2015 carried out a selfadministered questionnaire of 1,861 intensive care unit (ICU) staff in 23 tertiary hospitals in China and found that only 36.5% of physicians and 22% of nurses knew about the national VTE guidelines. Tang recognized that their study was only focused on one medical specialty which could have led to sample bias.…”
Section: Surveymentioning
confidence: 99%